2022
DOI: 10.3390/su14031364
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Green Marketing on Consumer Behavior in the Market of Palm Oil Products

Abstract: The aim of the article is to examine the impact of green marketing on consumer behavior in the market for products containing palm oil. The first chapter addresses the theoretical approach—the impact of green marketing on consumer behavior. We considered a questionnaire survey to be the most appropriate method to conduct our research. In order to test our hypotheses, we applied Crosstab and Pearson’s chi-square test. The strength of the relationship between the variables was measured using Cramer’s V. The thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 66 publications
5
20
0
1
Order By: Relevance
“…This also suggests that informational interpersonal influence susceptibility is an important way to reverse the formation regarding positive purchase intentions for GTTT products among price-conscious consumers, and it is thus a strategic path to cross the "chasm" in the market as a whole. These results are similar to those of Machová et al [74], who found that before specific product information was provided to consumers, consumers indicated that price was the most important factor compared to the brand, ingredients, and packaging of the product. However, after specific information about the product was provided, 58.7% of consumers indicated that they were willing to pay a higher price for green products.…”
Section: Discussionsupporting
confidence: 90%
“…This also suggests that informational interpersonal influence susceptibility is an important way to reverse the formation regarding positive purchase intentions for GTTT products among price-conscious consumers, and it is thus a strategic path to cross the "chasm" in the market as a whole. These results are similar to those of Machová et al [74], who found that before specific product information was provided to consumers, consumers indicated that price was the most important factor compared to the brand, ingredients, and packaging of the product. However, after specific information about the product was provided, 58.7% of consumers indicated that they were willing to pay a higher price for green products.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, according to the Flash Eurobarometer Survey, the lack of financial knowledge and the consideration of environmental engagement as an extra activity excluded from the core of the business strategy development are among the main barriers that hinder innovation. Considering Machová et al [24] study, in which they highlighted that environmental protection is not the most important factor and just a secondary option for Eastern European consumers, SMEs' repayment ability will not improve due to green innovative products. In other words, credit-constrained SMEs have neither sufficient financial resources nor lenders' support to invest in innovative projects and they lack the necessary financial knowledge to seize funding opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…The limited awareness of the opportunities and benefits of green innovation is a major reason [22,23]. Machová et al [24] and Chen et al [25] supported this stream of literature. They found that consumers purchase sustainable products if the products are marketed successfully.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Consumers who are concerned about caring for the environment are reluctant to consume products that require a high use of energy and resources to produce them, that generate intensive waste due to packaging or short shelf life, that use materials that negatively affect the inhabitants of the area, and also endanger their health or the health of others [45]. In recent years, a group of consumers committed to health and sustainability "LOHAS" has emerged, who are differentiating themselves by their healthy lifestyle and also try to satisfy their needs by acquiring products and/or services that do not harm the environment and society [45,46]; however, there is another sector of consumers who are not willing to spend time to read the description of the composition of the products they purchase, so a company that wants to contribute to sustainable development and launch eco-friendly products, should carry out efforts to educate consumers so that they are willing to buy environmentally friendly products [47].…”
Section: Background 21 Consumer Behavior In Developing Countries Seek...mentioning
confidence: 99%